INOVASI PENDIDIKAN DI SEKOLAH DASAR: MODEL RADEC DAN PENGARUHNYA PADA KEMAMPUAN PEMECAHAN MASALAH IPA SISWA 5 - Hany Handayani; Ihsan Rizali; Somantri, Mubarok; Rani Sukardi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Currently, 21st-century skills are needed for students, one of which is problem-solving skills. However, the learning process carried out by the teacher still tends to use the lecture method so that it cannot maximize students' problem-solving skills. To solve this problem, innovation is needed, namely the application of the RADEC learning model. The purpose of this study was to determine the effectiveness of the RADEC learning model in improving the problem-solving abilities of elementary school students. This study uses a quasi-experimental quantitative approach with a nonrandomized control group pretest-posttest design. The sample in this study was 5th-grade students at MI Pagelaran Kab. Purwakarta for the 2019/2020 school year a total of 40 students. Data were collected using the test, observation, and questionnaire techniques and then analyzed using quantitative analysis, namely the N-gain test to see improvement and the t-test to determine the effectiveness of the RADEC learning model on students' problem-solving abilities. The results showed that the learning process using the RADEC learning model was effective in improving problem-solving for 5th-grade elementary school students. The problem-solving ability of students has increased significantly after the implementation of learning using the RADEC learning model.